2012
DOI: 10.1093/molehr/gas036
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic moles and non-familial biparental moles are not caused by mutations in NLRP7, NLRP2 or C6orf221

Abstract: Hydatidiform moles (HMs) most often occur sporadically and are either diploid androgenetic or triploid. The very rare familial recurrent HMs (FRHMs) have been related to NLRP7 and C6orf221 mutations in the mother. FRHMs are most often diploid with both maternal and paternal origin of the molar genome. We have screened a cohort of 11 women with diploid HMs with biparental contributions to the molar genome with regard to mutations in NLRP7, NLRP2, the NLRP gene most homologous to NLRP7, and C6orf221. This was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Mutations in KHDC3 were found in women with familial diploid biparental hydatidiform mole s from four families [ 47 , 48 ] and in two unrelated women with diploid biparental hydatidiform mole s but without familial hydatidiform mole s [ 49 ]. However, discordant evidence seems to exclude mutations in this gene as a cause of non-familial biparental moles [ 50 ] and androgenetic moles [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in KHDC3 were found in women with familial diploid biparental hydatidiform mole s from four families [ 47 , 48 ] and in two unrelated women with diploid biparental hydatidiform mole s but without familial hydatidiform mole s [ 49 ]. However, discordant evidence seems to exclude mutations in this gene as a cause of non-familial biparental moles [ 50 ] and androgenetic moles [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also not been able to confirm the previously suggested association between mutations in NLRP7 and androgenetic or diandric triploid forms of HM, providing additional indication that BiHM have different origins than AnCHM and diandric triploid PHM. 14,21 The evolving lack of support for the involvement of these genes in adverse reproductive outcomes other than BiHM has important implications for clinical diagnostic testing for mutations in these genes, which may only be indicated in the presence of proven BiHM or highly recurrent HM (more than two) of unknown inheritance and genotype. Because most of these studies were carried out in relatively small cohorts, larger multicenter collaborative studies may be required to conclusively demonstrate that mutations in NLRP7 or KHDC3L in women are uniquely responsible for recurrent rare BiHM.…”
Section: Discussionmentioning
confidence: 99%
“… 12 One of these 3 cases (case 131) was part of an extensively studied family in which the mother carries mutations in both alleles of NLRP7 . 5 , 22 24 …”
Section: Methodsmentioning
confidence: 99%